PERAN EKONOMI ISLAM DALAM PENGENTASAN KEMISKINAN DAN PEMBERDAYAAN EKONOMI UMMAT - Mundir, Ahmad; Rosidi, M. Imron; Setianingrum, Nurul; Anggitaningsih, Retna (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2025)
Poverty is a complex social problem and a serious challenge for countries with a Muslim majority population. Islamic economics offers an approach based on the values of social justice, solidarity, and ethics to address this issue. Amidst global economic instability causing conventional financial institutions to fail, Islamic economics has shown resilience and significant growth. This study aims to analyze the role of Islamic economics in alleviating poverty and empowering the community’s economy. Based on principles outlined in the Quran, this research explores the concept of empowerment through two main approaches: social rehabilitation and community development. The findings indicate that the Islamic economic approach has the potential to improve the welfare of the poor through fairer and more sustainable empowerment mechanisms.